2015
DOI: 10.1002/mrm.25583
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent T2 relaxometry algorithm for myelin water imaging of the brain

Abstract: The Exponential Analysis via System Identification using Steiglitz-McBride algorithm provides an efficient and user-parameter-free alternative to non-negative least squares for estimating the parameters of multiple relaxation components and gives a new way of estimating the spatial variations of myelin in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
(73 reference statements)
0
18
0
1
Order By: Relevance
“…Detection and characterization of multiple components of relaxation in the brain are useful. A number of studies have demonstrated that several applications utilized multicomponent T 2 in assessing white matter pathology and myelin . The short‐ and long‐T 2 components in the biexponential T 2 relaxation model represent anatomical compartmentation of tissue water, probably intra‐ and extracellular water .…”
Section: Discussionmentioning
confidence: 99%
“…Detection and characterization of multiple components of relaxation in the brain are useful. A number of studies have demonstrated that several applications utilized multicomponent T 2 in assessing white matter pathology and myelin . The short‐ and long‐T 2 components in the biexponential T 2 relaxation model represent anatomical compartmentation of tissue water, probably intra‐ and extracellular water .…”
Section: Discussionmentioning
confidence: 99%
“…Parametric time-domain methods, due to their superior resolution, have been shown to surpass their nonparametric counterparts. [8] Several parametric estimators for multiple-damped exponentials-such as filter diagonalization method, [9] Hankel singular value decomposition, [10] Hankel total least squares, [6] complete reduction to amplitude frequency table (CRAFT), [11] and matrix pencil [12] have been shown to accurately quantitate and extract the parameters of the FID signal. [13] However, many of these methods (though not CRAFT) require the number of cisoids in the signal model to be known a priori, and this can introduce a systematic bias into their estimates.…”
Section: Prior Workmentioning
confidence: 99%
“…[15] This method has been shown to exhibit superior performance over most of the existing methods when applied to the extraction of T 2 relaxation parameters for myelin water imaging of the brain-a problem that employs such an exponential signal model. [8] Also, it has been shown to be completely user-input free. These advantages make the SM method an excellent choice for the extraction of FID parameters.…”
Section: Prior Workmentioning
confidence: 99%
See 2 more Smart Citations